2018
DOI: 10.1371/journal.pone.0195890
|View full text |Cite|
|
Sign up to set email alerts
|

Using the Normalization Process Theory to qualitatively explore sense-making in implementation of the Enhanced Recovery After Surgery programme: "It's not rocket science"

Abstract: IntroductionThe Enhanced Recovery After Surgery programme (ERAS) is an approach to the perioperative care of patients encompassing multiple interventions and involving a wide range of different actors. It can thus be defined as a complex intervention. Despite the strength of the evidence-base in its support, the implementation of ERAS has been slow. This paper specifically explores the utility of Normalization Process Theory (NPT) as a methodological framework to aid exploration of ERAS implementation, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 22 publications
0
31
0
1
Order By: Relevance
“…Stolldorf et al [ 99 ] Level of Institutionalisation Scale To determine the level of sustainability of rapid response teams (RRTs) among a group of hospitals that participated in a state-wide collaborative to implement and sustain RRTs United States Secondary Care 57. Sutton et al [ 100 ] Normalisation Process Theory To explore the utility of NPT as a methodological framework to aid exploration of Enhanced Recovery After Surgery (ERAS) programme implementation United Kingdom Tertiary Care 58. Thomas, L.H.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stolldorf et al [ 99 ] Level of Institutionalisation Scale To determine the level of sustainability of rapid response teams (RRTs) among a group of hospitals that participated in a state-wide collaborative to implement and sustain RRTs United States Secondary Care 57. Sutton et al [ 100 ] Normalisation Process Theory To explore the utility of NPT as a methodological framework to aid exploration of Enhanced Recovery After Surgery (ERAS) programme implementation United Kingdom Tertiary Care 58. Thomas, L.H.…”
Section: Resultsmentioning
confidence: 99%
“…The most common benefit reported from the use of sustainability approaches was the improved understanding of sustainability and sustainability constructs. Twenty-five articles stated they were able to improve conceptualisation of sustainability of interventions [ 47 , 48 , 50 , 53 , 54 , 58 , 61 , 71 73 , 75 , 78 80 , 86 , 88 , 92 , 95 , 96 , 100 , 101 , 103 , 104 , 110 ]. For example, Deconinck et al applied Atun’s Conceptual Framework for Analysing Integration of Targeted Health Interventions, and found that the approach provided a systems lens that increased understanding of pathways for integration to help sustain coverage of effective interventions [ 58 , 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our findings showed there was lack of clarity among local stakeholders regarding the scope of the programme, which is a crucial element for achieving successful implementation [46]. There was consensus that the programme was predominantly about embedding outcome measures and EBP into practice.…”
Section: The Programme Was Not Clearly Defined or Understoodmentioning
confidence: 79%
“…As previously identified, implementation science in the perioperative care setting is in its infancy Gramlich et al, 2017;Herbert et al, 2017;Lyon et al, 2014;. Barriers relevant to the intervention itself also exist, such as failure to adapt the guideline to the local context, degree of fit to an often diverse patient group and adoption of a segmental approach or 'over tailoring' of the intervention (Gramlich et al, 2017;Herbert et al, 2017;Lyon et al, 2014;Sutton et al, 2018), as well as a reported tension between standardised versus individualised care (Lyon et al, 2014). Cohesive, visible leadership and adequate ongoing multidisciplinary staff education are identified as enablers at the micro-level.…”
Section: Barriers and Enablers To Implementing Enhanced Recovery Aftementioning
confidence: 99%
“…At the meso-level (i.e. local and organisational context), lack of formal leadership support, unsupportive culture, limited stakeholder buy-in, complex systems and processes, and failure to establish ongoing audit and feedback processes were identified as barriers to implementation (Gotlib Conn et al, 2015;Gramlich et al, 2017;Herbert et al, 2017;Pearsall et al, 2015;Sutton et al, 2018), whereas embedding the change into existing systems and processes was an enabler (Herbert et al, 2017).…”
Section: Barriers and Enablers To Implementing Enhanced Recovery Aftementioning
confidence: 99%